MODERASI BERAGAMA SEBAGAI BASIS KEHIDUPAN SOSIAL: TELAAH FILOSOFIS DALAM ISLAM KONTEMPORER - Yuliana, Evi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
Religious moderation has become an important theme in social and religious discourse in the contemporary era, especially in the Islamic context. The research aims to explore the concept of religious moderation as the basis of social life, with a deep philosophical approach. In this context, religious moderation is not only understood as an attitude of tolerance between religious communities, but also as an approach that prioritises balance, justice and respect for differences. Data and statistics show that religion-based social conflicts are often fuelled by extremism and intolerance. Therefore, it is important to analyse how religious moderation can be a solution to create social harmony. In this study, the author will discuss various aspects of religious moderation, including the values contained in the Qur'an and Hadith that support the practice of moderation. In addition, the author will also present case examples from various countries that demonstrate the successful application of religious moderation in reducing conflict and increasing harmony. Through a philosophical approach, this research is expected to provide a deeper understanding of the role of religious moderation in building a harmonious and sustainable social life. By referring to valid references, this research will present a strong argument regarding the importance of religious moderation in an increasingly complex global context. This research is expected to be a contribution for academics, practitioners, and policy makers in an effort to promote the values of moderation in everyday life. Finally, it is hoped that the results of this study can serve as a reference for further research on religious moderation and its impact on social life in diverse societies